2012
DOI: 10.1111/j.1442-2042.2012.03091.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the response to treatment between Asian and Caucasian men with benign prostatic hyperplasia: Long‐term results from the combination of dutasteride and tamsulosin study

Abstract: Abbreviations & Acronyms 5AR = 5a-reductase 5ARI = 5a-reductase inhibitor AE = adverse events AUR = acute urinary retention BII = BPH impact index BMI = body mass index BPH = benign prostatic hyperplasia CombAT = Combination of Avodart and Tamsulosin IPSS = International Prostate Symptom Score LUTS = lower urinary tract symptoms PSA = prostate-specific antigen PV = prostate volume Qmax = maximum urinary flow rate QoL = quality of life SAE = serious adverse events Abstract: The Combination of Avodart and Tamsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Randomised controlled trials have shown that treatment with dutasteride reduces AUR and BPH‐related surgery in patients with BPH at risk of disease progression, and database studies indicate that earlier initiation of dutasteride prevents disease progression to a greater extent than later initiation . However, the appropriate timing of dutasteride initiation in Japanese patients with BPH has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Randomised controlled trials have shown that treatment with dutasteride reduces AUR and BPH‐related surgery in patients with BPH at risk of disease progression, and database studies indicate that earlier initiation of dutasteride prevents disease progression to a greater extent than later initiation . However, the appropriate timing of dutasteride initiation in Japanese patients with BPH has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Combined therapy of α1‐blockers and 5α‐reductase inhibitors is recommended for BPH with prostate volume >30 mL (level 1; grade A) . Superiority of combined therapy to monotherapy of 5α‐reductase inhibitors might be uncertain for BPH with prostates >60 mL …”
Section: Clinical Questionsmentioning
confidence: 99%
“…Another subanalysis of CombAT data revealed sustained superior therapeutic effect of combination treatment over tamsulosin monotherapy in improving LUTS, regardless of patients’ ethnic background. Even though racial differences in 5-AR activity, prostate volume, PSA levels and LUTS severity have been proved, no difference was found between Asian and White men in terms of clinical response to treatment [Chung et al . 2012].…”
Section: Rationale For Combined Usementioning
confidence: 99%